Karakterisasi Morfologi dan Potensi Hasil Durian Lokal Bangka - Mustikarini, Eries Dyah; Khodijah, Nyayu Siti; Yulistia, Yulistia (Universitas Bangka Belitung, 2017)
Durian is a plant that susceptible to genetic erosion. Exploration and characterization of Bangka local durian need to be protected germplasm of Bangka local durian. This research aims to characterize the morphology, determine the relationship, and yield of Bangka local durian. The research had been conducted in December 2011 to February 2012 in West Bangka, Central Bangka, and South Bangka regency. The research methods were exploration, identification, and characterization. The result shows there are 11 accessions from West Bangka, 11 accessions from South Bangka and 5 accessions from Central Bangka. Similarity analysis using quantitative and qualitative characteristics divides into five groups at 60% similarity level. The average yield of Bangka local durian about 40-250 fruits/year. Sigajah accession has the highest yield potency with average fruit weight of 2.3 kg and 60-140 fruits/plant.